Bridging the Gap: Policy Strategies to Align UIN Salatiga Research with Regional Needs - Yusuf Ismail (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper describes that low utilization of UIN Salatiga's outputs by industry, society, and government is a pressing challenge that creates a gap between academic research and practical implementation. This phenomenon is rooted in a lecturer performance evaluation system that tends to be quantitative and publication-oriented, rather than focused on real impact. As a result, many high-quality research results remain merely theoretical documents, without making significant contributions to development or solving problems in the field. This policy article aims to comprehensively analyze this issue. The writing method used is qualitative policy analysis, with a diagnostic and prescriptive approach. The initial step is to identify the issue by formulating the problem, its causes, and its consequences based on secondary data and relevant theoretical frameworks, such as Agency Theory and the Goal Substitution Concept. Next, an analysis of policy alternatives is conducted to identify feasible and effective intervention options, using the William N. Dunn scoring method. This analysis yields a single recommendation, deemed the most optimal, namely a revision of the university's internal regulations. This recommendation focuses on changes to the incentive system, which are then formulated into specific policy proposals addressed to key stakeholders. The overall process aims to provide practical and theoretical guidance for transforming the research ecosystem at UIN Salatiga.